Student life in a class society. - Abbott, Joan (Pergamon Press, 1971)
Student Life in a Class Society covers specific topics within the general field of social anthropology. This book discusses the social class composition and influence in the student body of the University of Edinburgh, as well as the motives of students entering the university.